PERLINDUNGAN HUKUM TERHADAP HAK WARGA NEGARA DALAM KARYA BUKU ELEKTRONIK (E-Book) - Laylia Selsi Qodri Gusti; Elsy Renie; Zainuddin Zainuddin; Siska Elasta Putri (JISRAH: Jurnal Integrasi Ilmu Syariah, 2023)
This study examines the legal protection of citizens' rights in electronic book works (e-books), there are still many violations of citizens' rights in the form of piracy of electronic book works (e-books). The problem is the regulation given by the state to the legal protection of citizens' rights in electronic book works (e-books) so that electronic books (e-books) are perfectly protected and the government's role in the legal protection of citizens' rights in electronic book works (e-books). This research is library research. Data and materials are obtained through reading, citing books, researching, analyzing documents, news on the internet and laws related to discussion. After the data / material is collected, it is processed in a descriptive qualitative way and analyzed in a deductive. This study found that existing laws and regulations have not protected electronic books (E-books) as a whole, so changes are needed so that electronic books (e-books) can be perfectly protected.